Stratigraphy and sedimentary environment of late Middle - Early Late Miocene Chiang Muan formation, Phayao Province, Thailand - Akira Fukuchi (2018)
The sedimentary facies analysis shows that the late Middle - early Late Miocene Chiang Muan Formation can be subdivided into five members: the Sa Nua Mudstone Member (Sa Nua Member), the Sa Tai Lignite Member (Sa Tai Member), the Sa Sandstone and Conglomerate Member (Sa Member), the Kon Lignite Member (Kon Member) and the Thung Nong Mudstone and Sandstone Member (Thung Nong Member) in ascending order. The mammalian fossil-bearing horizons are in the Sa Tai and Kon members. Each member is represented by unique sedimentary environments resulted from the changes of fluvial systems, which are expressed by braided-river and meandering-river facies associations. The braided-river facies association characterized by multiple synchronous channels, consisting of channel-fill and floodplain deposits, is recognized in the Sa Member. The meandering-river facies association is composed of the finer-grained sediments, including lignite. A channel, floodplain and fen/marsh environments can be recognized in this facies association. It is recognized in the Sa Nua, Sa Tai, Kon and Thung Nong members.